Pengaruh Kombinasi Dosis Pupuk Kascing dan Pupuk Urea Terhadap Pertumbuhan dan Hasil Bawang Merah (Allium ascalonicum L.) Varietas Bima Brebes - Fauzianingsih, Rika; Sugiono, Darso; Supriadi, Devie Rienzani (JURNAL AGROPLASMA, 2023)
Shallot (Allium ascalonicum L.) is a type of vegetable plant that is widely planted in several regions in Indonesia which is used as a cooking spice and has ingredients that are beneficial to health. Fulfillment of nutrient needs for growth and yield in plants can be done by fertilization. The aim of this study was to determine the effect of a combination of doses of vermicompost and urea fertilizer on the growth and yield of the Bima brebes variety of shallot (Allilum ascalonicum L.). The research was carried out in Karangmangu Village, Kec.Kramatmulya, Kab. Kuningan, West Java. The experiment was carried out in March 2023 – May 2023. The study used a Single Factor Randomized Block Design (RBD) consisting of 10 treatments repeated 3 times, consisting of 10 treatments namely A (20 tonnes/ha of cow manure+400 kg/ha of urea +200 kg/ha phonska), B (10 tonnes/ha vermicompost+200 kg/ha urea), C (10 tonnes/ha vermicompost+300 kg/ha urea), D (10 tonnes/ha vermicompost+400 kg/ ha urea), E (15 tonnes/ha vermicompost+200 kg/ha urea), F (15 tonnes/ha vermicompost+300 kg/ha urea), G (15 tonnes/ha vermicompost+400 kg/ha urea), H (20 tonnes/ha vermicompost+200 kg/ha urea), I (20 tonnes/ha vermicompost+300 kg/ha urea), J (20 tonnes/ha vermicompost+400 kg/ha urea). The results showed that there was a significant effect of the combination doses of vermicompost and urea fertilizer on the growth and yield of the shallot (Allium ascalonicum L.) variety Bima brebes on plant height, number of leaves, tuber wet weight, tuber diameter, and tuber dry weight. Treatment J (20 tonnes/ha vermicompost+400 kg/ha urea) gave the highest yield on tuber dry weight of 38.33 g.